IMPLEMENTATION OF SOUNDSCAPE AT RAIL BOUNDARIES, CASE STUDY JL. HAUR JAYA, BOGOR CITY - Nyi Raden Ajeng Putri Anggiandari; Mokhammad Syaom Barliana; Diah Cahyani Cahyani (Universitas Pendidikan Indonesia, 2022)
Bogor is an area that accommodates the needs of the capital city of Jakarta (Wilza et al., 2021), this high population rate has contributed to dense settlements to facilitate their lives and activities, for people who have financial limitations choose an alternative to building their homes on the railroad tracks (Prihatiningsih Rahmawati, 2018). The railway line is supposed to function as a 10-meter-wide vacant land where 6 meters of this border is supposed to be used to reduce noise pollution by using a noise barrier to achieve a standardized noise level in settlements of 55Db(A) ( Department of Public Works, 2005). The outdoor acoustic environment is a diversity that is managed and enhanced, to control noise from the environment (Brown, 2010). With the Descriptive Analysis method on Jalan Haur Jaya, Bogor City. Noise data was taken with the SANFIX type WT85B Sound Level Meter instrument with a measurement time of 24 hours carried out 4 times at 4 measurement points. Soundscape is a solution to improve the quality of living comfort by applying the right arrangement of plants to reduce noise pollution, shade, absorb air pollution, windbreaker and view barrier (Syahindra et al., 2014) in this settlement obtained Leq 100.2 dBA, with the applied plant composition able to reduce noise by 48.25 dBA, this settlement meets the standard of residential noise.